An Appraisal of the Legal Framework for the Recognition and Enforcement of Foreign Judgments and International Arbitral Awards in Nigeria - Emmanuel, Sani (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
The judgment of a forum court is practically worthless in another jurisdiction, except it is recognised by the court of the foreign jurisdiction. In a bid to circumvent the challenges that this may pose, international businessmen, the world over, now resort to arbitration to settle their disputes, but paradoxically the arbitral process including the award depends on national legal orders for their validity and effectiveness. Another dimension to the challenge, becomes apparent when enforcement is sought against the properties of State counter-parties. The study which was based on a doctrinal research methodology, interrogated the extant laws in Nigeria, and it was observed that foreign judgments, foreign and international awards are enforceable in Nigeria based on both statutory and treaty regimes. Unlike foreign judgment which depends on the principle of reciprocity and comity enshrined in domestic conflict of laws which is fraught with procedural uncertainties, arbitral awards are covered by treaty regimes, and therefore enhances certainty and predictability of enforcement. The United Nations Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958), and the International Convention on the Settlement of Investment Disputes between States and Nationals of other State (1965), are instructive in that regard. However, enforcement in that context, is characterised by a regime of information asymmetry, as between both jurisdictions, which can open the flood gate for abuse. A policy and legislative framework, is therefore required to bridge the gap, and create a system of authentication of foreign judgment and arbitral awards, beside the extant provision for minimal judicial review.